Women, Media, and Information/Communication Technology - Tripon, Ma. Olivia H. (Review of Women's Studies; Vol 25 No 1-2 (2015): Review of Women's Studies Volume XXV, Numbers 1-2 (January-December 2015), 2018)
Strategic Objectives: J1. Increase the participation and access of women to expression and decision-making in and through the media and new technologies of communication J2. Promote a balanced and non-stereotyped portrayal of women in the media